2001
DOI: 10.1002/jms.212
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐phase conversion of tetrazoles to oxadiazoles: isolation and characterization of the N‐acylated intermediate

Abstract: The 5-substituted tetrazole ring was reacted in the gas phase with an acyl ion generated as the secondary reactive chemical ionization plasma in the mass spectrometer. The product ions obtained, among others, were proposed as the rearranged 2,5-disubstituted-1,3,4-oxadiazole nucleus. Its structure was demonstrated by comparison of the product ion spectrum of the 2,5-disubstituted-1,3,4-oxadiazole derivative obtained by condensed-phase reaction and the product ion spectrum of the oxadiazole derivative generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The mass spectrometric fragmentation pathways of 1,3,4-oxadiazoles were studied by electron ionization (EI) [1][2][3], chemical ionization (CI) [4], electrospray ionization (ESI) [5] and liquid secondary ion mass spectrometry (LSIMS) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The mass spectrometric fragmentation pathways of 1,3,4-oxadiazoles were studied by electron ionization (EI) [1][2][3], chemical ionization (CI) [4], electrospray ionization (ESI) [5] and liquid secondary ion mass spectrometry (LSIMS) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The EI-induced decomposition of 1,3,4-oxadiazoles was also studied [9][10][11] and complex skeletal rearrangement, consisting of the elimination of N 2 and CO molecules proceeded, leading to the formation of fluorene-type ions ([M -CO -N 2 ] +• ions). 10,11 Mass spectrometric fragmentation pathways of 1,3,4-oxadiazoles were also investigated by using so-called soft ionisation techniques such as chemical ionisation (CI), 12 electrospray ionisation (ESI) and liquid secondary ion mass spectrometry (LSIMS). 13,14 It was shown that protonated molecules of 2,5-diaryl-1,3,4-oxadiazoles lose isocyanic acid (HNCO) through complex skeletal rearrangement ([R -CN -R] + ions).…”
Section: Introductionmentioning
confidence: 99%
“…[11] A literature survey showed that few reports are available on mass spectral fragmentation of oxadiazole derivatives. [12][13][14][15][16][17][18][19] As these compounds belong to the category of organic light-emitting diodes (OLEDs) containing an oxadiazole group, the fragmentation behavior of these compounds under mass spectrometric conditions assumes importance and is desirable. These mass spectral studies may help in understanding the degradation process of these materials and in turn their stability and life.…”
mentioning
confidence: 99%